2011
DOI: 10.1021/tx200394g
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Methylmercury by Hydrogen Sulfide-Producing Enzyme in Mammalian Cells

Abstract: Methylmercury (MeHg) covalently modifies cellular proteins through their SH groups, resulting in cytotoxicity. We report that cystathionine β-synthase (CBS), which catalyzes the production of hydrogen sulfide, contributes to cellular protection against MeHg. Pretreatment with NaHS or overexpression of CBS reduced MeHg cytotoxicity, whereas transfection with CBS small interfering RNA enhanced MeHg toxicity in human neuroblastoma SH-SY5Y cells. Bismethylmercury sulfide ((MeHg)(2)S) was identified as a metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 11 publications
1
67
0
Order By: Relevance
“…Taken together, the results suggest that RSS derived particularly from CSE play critical roles in regulating activation of the cellular signaling pathway by cadmium and in protecting against cadmium toxicity, presumably via the inactivation of cadmium within the cells. We have previously found that MeHg reacts with RSS to form the detoxified metabolite (MeHg) 2 S (Abiko et al, 2015;Yoshida et al, 2011). Sulfur adducts formed with cadmium have yet to be identified, but we speculate that RSS can trap cadmium to form inert sulfur adducts, protecting cells from cadmium injury.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Taken together, the results suggest that RSS derived particularly from CSE play critical roles in regulating activation of the cellular signaling pathway by cadmium and in protecting against cadmium toxicity, presumably via the inactivation of cadmium within the cells. We have previously found that MeHg reacts with RSS to form the detoxified metabolite (MeHg) 2 S (Abiko et al, 2015;Yoshida et al, 2011). Sulfur adducts formed with cadmium have yet to be identified, but we speculate that RSS can trap cadmium to form inert sulfur adducts, protecting cells from cadmium injury.…”
Section: Discussionmentioning
confidence: 90%
“…RSS have strongly nucleophilic properties compared with the parent nucleophiles, so it is likely that RSS will readily trap environmental electrophiles, forming sulfur adducts of the electrophiles. Consistent with this, MeHg reacts with RSS (eg, hydrogen sulfide, GSSH, GSSSG) forming bismethylmercury sulfide, which is not electrophilic and is not very toxic (Abiko et al, 2015;Yoshida et al, 2011). We therefore hypothesized that RSS will modulate the cadmiummediated activation of redox signal transduction pathways such as the HSP/HSF1 pathway and modulate cadmiuminduced cytotoxicity by capturing cadmium.…”
mentioning
confidence: 88%
“…In contrast, (MeHg) 2 S itself was not toxic to mice when injected intraperitoneally. 12 Taken together, it seems likely that the capture of MeHg by reactive sulfide derivatives formed endogenously to produce (MeHg) 2 S plays a key role in detoxifying MeHg. While GSH is abundant (>1 mM) in a range of tissues, it has a pKa of 9.12 which indicates that the free anionic GS − is a minority species at physiological pH.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Indeed, we found that MeHg interacts with sodium hydrogen sulfide (NaHS) to produce bismethylmercury sulfide (MeHg) 2 S in in vitro experiments and that (MeHg) 2 S is formed in MeHg-treated SH-SY5Y cells and liver extracts of rats intraperitoneally injected with MeHg. 12 There are numerous sulfur-containing low-molecular-weight compounds in the body, including cysteine (CysSH), cystine (CysSSCys), GSH, glutathione disulfide (GSSG), methionine (Met), and sulfate ions (SO 4 2− ). 13 We recently found that some persulfide species in mammalian cells and tissues such as Cys persulfide (CysSSH), Cys polysulfides (CysSS n SH), GSH persulfide (GSSH), and GSH polysulfides (GSS n SH) contain highly reactive nucleophilic sulfur groups and have antioxidant activities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Intracellular factors that contribute in reducing MeHg toxicity [i.e., transcription factors such as nuclear factor-E2-related factor 2 (Nrf2) 11) and heat shock factor protein 1 (Hsf1) 12) as well as in vivo metabolites such as hydrogen sulfide (H 2 S) 13) ] have been identified. This proved the existence of novel biological defense mechanisms against MeHg toxicity.…”
Section: Introductionmentioning
confidence: 99%